Sperms Abnormalities and Testicular Damage Induced by cyclosporine A Drug and the Protective Effect of Garlic in Male Albino Rats - Jasim, Shaimaa Mohammed Ali; Mohammed, Zaid Makki; AL-Nahi, Alaa Shakir (Iraqi Journal of Science, 2023)
The objective of present study is to identify the adverse effects of cyclosporine A drug and the protective role of garlic in cytotoxicity test, including sperms deformation and histological changes in testes tissues of male albino rats. The study recorded significant increase p≥0.05 in sperms head and tail deformation rates in groups that were administrated cyclosporine and cyclosporine + garlic for two weeks compared with control groups which were administrated olive oil and garlic. The study reported significant decrease p≥0.05 in sperms head and tail deformation rates in the group that was administrated cyclosporine + garlic compared with group that was administrated cyclosporine only. In addition, the study also indicated histological changes in testes tissues including degenerative changes represented by depletion of the spermatogonial cells (some seminiferous tubules appeared with one or two layers of spermatogonia) in the group that was administrated cyclosporine compared with the control group which was administrated olive oil. The study reported slight histological changes in testes tissues from normal testes architecture, somniferous tubules with maturation of spermatogony and sperms inside the lumen in group that was administrated cyclosporine + garlic for two weeks compared with the control group which was administrated olive oil and garlic. Finally, the findings showed reduction in histological changes of testes tissues in group which was administrated cyclosporine + garlic for two weeks compared with group which was administrated cyclosporine only.